Direct and indirect comparisons in network meta-analysis of SuperPATH, direct anterior and posterior approaches in total hip arthroplasty - Nikolai Ramadanov; Simon Bueschges; Kuiliang Liu; Philip Lazaru; Ivan Marintschev (Scientific Reports, 2022)
Abstract SuperPATH is a novel approach to the hip joint that needs to be compared to other known surgical approaches. To conduct a network meta-analysis (NMA) of randomized controlled trials (RCTs) comparing short-term outcomes of SuperPATH, direct anterior (DAA), and posterior/ posterolateral approaches (PA) in total hip joint arthroplasty (THA). We performed a systematic review on PubMed, CNKI, Embase, The Cochrane Library, Clinical trials, and Google Scholar up to November 30th, 2021. We assessed treatment effects between SuperPATH, DAA, and PA by performing a frequentist NMA, including a total of 20 RCTs involving 1501 patients. SuperPATH showed a longer operation time (MD = 16.99, 95% CI 4.92 to 29.07), a shorter incision length (MD = −4.71, 95% CI −6.21 to −3.22), a lower intraoperative blood loss (MD = −81.75, 95% CI  −114.78 to −48.72), a higher HHS 3, 6 and 12 months postoperatively (MD = 2.59, 95% CI 0.59–4.6; MD = 2.14, 95% CI 0.5–3.77; MD = 0.6, 95% CI 0.03–1.17, respectively) than PA. DAA showed a higher intraoperative blood loss than PA and SuperPATH (MD = 91.87, 95% CI  27.99–155.74; MD = 173.62, 95% CI 101.71–245.53, respectively). No other relevant differences were found. In conclusion, the overall findings suggested that the short-term outcomes of THA through SuperPATH were statistically superior to PA. DAA and PA as well as SuperPATH and DAA showed indifferent results.